THE ROLE OF TONES IN MODERN MANDARIN CHINESE: PHONETIC AND COMMUNICATIVE FUNCTIONS - Raimkhonova Lobar Farkhod kizi (Modern American Journals, 2025)
This paper explores the dual role of tones in Modern Mandarin Chinese as both phonetic and communicative elements of the language. Mandarin Chinese, as a tonal language, relies heavily on pitch variations to distinguish lexical meanings and convey pragmatic nuances. The study analyzes the acoustic properties, perceptual mechanisms, and communicative functions of Mandarin tones based on linguistic data and recent phonetic research. Findings indicate that tonal contrasts not only determine lexical distinctions but also serve as a crucial component in prosody, emotion, and discourse organization. The paper concludes that tones play an integrative role in shaping Mandarin’s sound system and communicative efficiency.
Keywords: Mandarin Chinese, tones, phonetics, communication, prosody, intonation.